Comparison of the Accuracy of GIS-Based Maps for Multi-Hazards in the Bandung-Cirebon High-Speed Railway Route Plan Phase I (Rancaekek-Cimalaka) - Aghastya, Adya; Hafid Hanafi, Afan; Apriliani, Nurul Fitria (SAINSTECH NUSANTARA, 2025)
Indonesia’s location within the Pacific Ring of Fire makes it highly vulnerable to natural disasters such as earthquakes, floods, and landslides. This study analyzes disaster vulnerability along the planned Phase I route of the Bandung–Cirebon High-Speed Railway (Rancaekek–Cimalaka) using Geographic Information System (GIS) tools. The analysis includes hazard mapping for landslides, floods, and earthquakes, as well as multi-hazard classification and accuracy assessment. Results show 73 high-risk landslide points, 20 earthquake-prone locations, and 47 multi-hazard zones, primarily concentrated in segments DK 1–5, DK 10–32, and DK 29–33. These findings underscore the need for targeted mitigation and resilient infrastructure planning.